Optimization of Using Cow's Manure Fertilizer at Different Rates on Growth and Production of Salvinia sp as Forage Feed - Uti Nopriani; Yusuf Randi Maugo; Juni Sumarmono (Jurnal Ilmu Ternak, 2022)
Salvinia sp is a high-quality aquatic plant with a high potential forage source for animals. The purpose of this study was to determine the effect of the use of cow manure on the growth and production of Salvinia sp crops. The variables in this study are leaf cover area (LCA), replication time, leaf diameter, and biomass production of Salvinia sp plants. The design used in this study was a completely randomized design (CRD) with four treatments of cow manure as fertilizer, consecutively: without manure; 5 g/L; 10 g/L; and 15 g/L. Each treatment has five replicates. The results showed that cow manure fertilizer significantly increased leaf cover area, replication time, leaf diameter, and biomass production of Salvinia sp. Cow manure fertilizer at a rate of 15 g/L is the best treatment. Increase in leaf cover area = 557.48 cm;  replication time = 2.99 days;  fresh weight = 8.80 g;   dry matter = 0.72 g. Results of linear regression analysis showed that the replication time of leaf cover area had a significant relationship with crop biomass production of Salvinia sp.Keywords: Growth, Production, Cow Manure Fertilizer, Salvinia sp